2016
DOI: 10.1002/ps.4221
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal activity of natural and modified triterpenoids against Aedes aegypti (Diptera: Culicidae)

Abstract: BA, UA and their derivatives showed larvicidal activity against Ae. aegypti larvae, increasing significantly from 48 to 96 h. The presence of a hydroxyl group is essential for larvicidal potential in these triterpenoids. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The eggs were allowed to hatch in an enamel bowl lined with Whatman filter paper filled with distilled water. The pupae formed were separated and transferred to insectary for the emergence of adults (da Silva et al, 2016[6]).…”
Section: Methodsmentioning
confidence: 99%
“…The eggs were allowed to hatch in an enamel bowl lined with Whatman filter paper filled with distilled water. The pupae formed were separated and transferred to insectary for the emergence of adults (da Silva et al, 2016[6]).…”
Section: Methodsmentioning
confidence: 99%
“…Their corresponding structures are illustrated in Figure 5. Bioassays of their chemical derivatives, with esterification of the hydroxyl group at the C-3 position, demonstrated less activity, suggesting that the hydroxyl group plays an important role in larvicidal activity [126].…”
Section: Terpenesmentioning
confidence: 99%
“…Molecular modeling techniques were also applied to establish a quantitative structure-activity relationship (QSAR). 57,[67][68][69][70] Structure-activity relationship studies were performed for acetogenins emphasizing the inhibition of the mitochondrial I complex. Data revealed that the presence of 1 or 2 tetrahydrofuran (THF) rings would have similar inhibitory effect.…”
Section: Structure-activity Relationshipmentioning
confidence: 99%
“…69 Larvicidal activity observed for both betulinic and ursolic triterpenic acids revealed that the presence of the hydroxyl group in C-3 is fundamental, as the esterification of hydroxyl decreases this activity. 57 By using QSAR method, a study was recently carried out, specifically for 61 plant-derived compounds known to have A. aegypti larvicidal activity. Compounds of the terpene class, phenylpropanoids, ketones, and oxygenate compounds were selected for the study.…”
Section: Structure-activity Relationshipmentioning
confidence: 99%